INFESTATION RATE OF ALMOND SEED WASP (EURYTOMA AMYGDALI ENDERLEIN, HYMENOPTERA: EURYTOMIDAE) ON IMPORTANT COMMERCIAL ALMOND VARIETIES IN MALATYA PROVINCE (TURKEY) - Yiğit, Talip; Özgen, İnanç; Canbay, Adnan; Koç, İbrahim (My University, 2020)
Almond seed wasp (Eurytoma amygdali Enderlein) (Hymenoptera: Eurytomidae) is one of the most important pests of almond. Pest’s infestation ratio can be as high as 95% in some areas in case if the pest is not tackled. The study was conducted to determine the preferences of Almond seed wasp seed wasp for some almond varieties (Ferragnes, Ferraduel, Nonpareil, Drake, Cristomorto and Garrigues) in the years 2017 and 2018. Furthermore, times of emerging of the pest in Malatya Province and the number of individuals emerging from damages fruits based on years were determined. Cage observations were carried out and fruits were counted under field conditions and results were discussed with meteorological data. As a result of the study, it was found that the lowest infestation rate of E. amygdali was in Ferragnes variety (81%) followed by Cristomorto variety (85%) while the highest infestation rate was found in Nonpareil variety (97%). While the rate of emerging of the pests as adults in 2017 was 89.3%, rate of individuals passing down to the next generation was 10.6%. It was found in the study that the time of emergence as adults of Almond seed wasp seed wasp in Malatya was the end of April when the maximum air temperature was 25oC and the daily mean temperature is higher than 15oC, and when the temperatures are routinely around these levels.
Keywords: Entomoloji